2011
DOI: 10.5172/conu.2011.39.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and linguistic isolation: The breast cancer experience of Chinese-Australian women – A qualitative study

Abstract: In providing information for Chinese-Australian women with breast cancer, culture, language and migration experience need to be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 2 publications
8
77
0
Order By: Relevance
“…The review suggests that many breast cancer survivors and patients believe that stress contributes to the development of breast cancer. Despite the lack of evidence that stress causes cancer, sixteen studies found that women attributed their breast cancer to their experience of stress [9,13,15,16,24,[35][36][37][38][40][41][42][43][50][51][52].Moreover, stress was identified as the leading cause of breast cancer in five studies [15,35,37,38,42]. In a study by Oba et al, [35] 70% (n=44) of the sample attributed their cancer to stress.…”
Section: Causal Attributions Identified But Not Validated By Expert Cmentioning
confidence: 99%
See 4 more Smart Citations
“…The review suggests that many breast cancer survivors and patients believe that stress contributes to the development of breast cancer. Despite the lack of evidence that stress causes cancer, sixteen studies found that women attributed their breast cancer to their experience of stress [9,13,15,16,24,[35][36][37][38][40][41][42][43][50][51][52].Moreover, stress was identified as the leading cause of breast cancer in five studies [15,35,37,38,42]. In a study by Oba et al, [35] 70% (n=44) of the sample attributed their cancer to stress.…”
Section: Causal Attributions Identified But Not Validated By Expert Cmentioning
confidence: 99%
“…Four out of the sixteen studies which reported stress-related attributions for breast cancer, specifically defined stress as an inability to cope with a stressful situation, such as relationship conflicts, experience of trauma, dealing with loss or grief, and/or coping with a demanding environment [13,38,42,50]. Some women may rationalize stress as an attribution that is beyond their control.…”
Section: Causal Attributions Identified But Not Validated By Expert Cmentioning
confidence: 99%
See 3 more Smart Citations